PENGARUH AROMATERAPI JAHE (Zingiber officinale) TERHADAP MUAL MUNTAH PASIEN KANKER PASCA KEMOTERAPI - yauwan Tobing Lukiyono tobing; Ersalina Nidianti; Salfa Salsabilah Zain (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2023)
Chemotherapy is a medical procedure used to stop the growth of cancer cells. Chemotherapy involves injecting or ingesting chemicals. Cytotoxic chemotherapy cause unpleasant side effects like nausea and vomiting. Non-pharmacological therapies, such as combination therapy with ginger aromatherapy and progressive muscle relaxation, can be used to treat nausea and vomiting. By lowering or stopping nausea and vomiting, ginger aromatherapy can be comforting. This study used the literature method by analyzing various sources from previous Â research which are then used as reference material for making this article. The results obtained were that the ginger aromatherapy inhibits serotonin receptors, which prevents serotonin released and contractions of the stomach muscles, hence reducing nausea and vomiting. The conclusion obtained is that ginger aromatherapy has been proven to have a calming effect and make a person relax. The compounds present in ginger such as zingiber and zingiberol have anti-emetic effects which can prevent nausea and vomiting.